(untitled) (International relations and international law Journal, 2025)
The global geopolitical landscape has undergone a transformation since the events of the late 20th century, marking the end of the bipolar system. Traditional paradigms are being replaced and transformed. The structure of intergovernmental relations, the interconnectedness of domestic and foreign policy, and their integration into regional and global processes have complicated the global system as a whole. We are witnessing an unprecedented level of global tension that has taken on a distinctly geopolitical character. These processes have not bypassed the European Union (EU). The nature and specificity of the EU’s functioning and its political processes in a globalizing world are also marked by rapid changes in the social, economic, energy, and political spheres. As the continent has long been in a state of strategic uncertainty and multifaceted crisis, the EU is now compelled to reconsider its worldview, its priorities, and its political strategy. In this complex period for Europe, the region of Central Asia is gaining significant geopolitical importance as a bridge between Europe and Asia. Pursuing its interests in the region, the EU has been developing strategies for Central Asia that outline its relations not only with the five Central Asian republics (Kazakhstan, Kyrgyzstan, Turkmenistan, Tajikistan, and Uzbekistan), but also seek to incorporate Afghanistan into the regional agenda. This is aimed at supporting efforts to stabilize the EU’s neighborhood in Central Asia. This paper attempts to analyze the reasons behind the ineffectiveness of previous strategies and the factors that influenced the EU’s reassessment of its position in the Central Asian region. Keywords: European Union, Central Asia, EU Strategy for Central Asia, democratization, Afghanistan, EU interests, great power rivalry.